Influence of Germany's monetary policy on the monetary policy of the EU - Romana Mikhel (Cхід, 2013)
The article outlines the main stages of the European monetary system formation and the role of the Federal Republic of Germany in it. German Central Bank is the most stable central bank among banks in the other EU Member States. Based on historical facts, the author examines the impact of monetary policy of Germany on the formation of the EU monetary policy.